Parental choices and outcomes in intercountry adoption - Martin, Nicole G; Salain, Meghan; Jackson, Daezha (Adoption & fostering, 2025)
This research explored the choices 473 intercountry adopting couples made regarding their desired attributes in a future child and the adoptive parents’ satisfaction regarding these choices a year after completing their adoption. Families were assessed prior to being matched with a child and asked to identify which characteristics were most important to them. Families most often specified a desired gender, age, ethnicity, country of origin and special needs status of their future children. Most important to them was specifying the child’s home country and the needs status, followed by being able to select the age of the child. A year after completing their adoptions, specifying more child characteristic criteria pre-adoption correlated with lower satisfaction and more regrets regarding their adoptions. Parents reported more regret with their adoptions and the process when they specified ethnicity, gender and age (under two years) and more satisfaction when they specified the needs status of the child. Strong preference for specific attributes in future children was related to lower satisfaction and regret post-adoption. Plain language summary This research explored the choices 473 intercountry adopting couples made regarding their desired attributes in a future child and the adoptive parents’ satisfaction regarding these choices a year after completing their adoption. Parents reported more regret with their adoptions when specifying ethnicity, gender and age. Parental openness to potential child characteristics may increase feelings of satisfaction post-adoption.